(untitled) (Romano-arabica, 2025)
This study aims to elucidate aspects of verbal periphrases involving kān in Colloquial Egyptian Arabic, drawing on excerpts from the speeches of former president Gamal Abdel Nasser. The theoretical framework relies on key studies, including Woidich’s Das Kairenisch-Arabische. Eine Grammatik and Eisele’s Arabic Verbs in Time: Tense and Aspect in Cairene Arabic. Given the frequent occurrence of these periphrases in conditional constructions, this paper will examine the relationship between conditional clause types and the associated periphrasis. Particular attention will be paid to the imperfective form bi + p-stem as it appears in kān periphrases.